Aliran Parnasianisme dan Sejarah Perkembangannya - Ilham Rozaq Al As'at (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2022)
Through this paper, researchers will seek to decipher (a) how the history of the emergence of parnasianism as a literary school, (b) who are the most important figures and poets of the Parnasianism school, (c) how the pattern of thought of the parnasianism school views a literary work. This type of research is qualitative research. The object of this study is the school of Parnasianism. The research method in this study is descriptive qualitative. At the data collection stage, researchers use the literature study method and use the note-taking method. The result of this study is that (a) the school of Parnasianism emerged as a form of reaction to the previous literary school and this school believed that art for art, meaning that a literary work was created as nothing but art. (b) Notable figures in this school were Theophile Gautier (1811-1872), Charles Baudelaire (1821-1867), Benjamin, Coffstan, Viktor Cousin (1792-1867), Gustave Flaubert (1821-1880), Leconte de Lisle (1818- 1894). (c) Parnasianism was born as a literary school that believed in freedom in literature and yearned for an aesthetic of any kind without regard to norms.